2023
DOI: 10.3390/tomography9030073
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pneumonia with Migratory Pattern in Agammaglobulinemic Patients: A Report of Two Cases and Review of Literature

Abstract: X-linked agammaglobulinemia (XLA) is a primary immunodeficiency characterized by marked reduction in serum immunoglobulins and early-onset infections. Coronavirus Disease-2019 (COVID-19) pneumonia in immunocompromised patients presents clinical and radiological peculiarities which have not yet been completely understood. Very few cases of agammaglobulinemic patients with COVID-19 have been reported since the beginning of the pandemic in February 2020. We report two cases of migrant COVID-19 pneumonia in XLA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our observations align with a hypothesis stemming from a report on patients with XLA, which suggests that this migratory phenomenon is likely a result of a lack of immune-mediated response due to impaired humoral (B-cell) immunity, which hinders the establishment of a proper inflammatory reaction in the lungs [ 14 ]. Interestingly, in patients with migratory pneumonia, we seldom observed parenchymal bands or reticular opacities in areas where opacities previously existed on CT scans.…”
Section: Further Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our observations align with a hypothesis stemming from a report on patients with XLA, which suggests that this migratory phenomenon is likely a result of a lack of immune-mediated response due to impaired humoral (B-cell) immunity, which hinders the establishment of a proper inflammatory reaction in the lungs [ 14 ]. Interestingly, in patients with migratory pneumonia, we seldom observed parenchymal bands or reticular opacities in areas where opacities previously existed on CT scans.…”
Section: Further Discussionsupporting
confidence: 90%
“…Interestingly, all patients who had used anti-CD20 agents within one year exhibited migration of airspace opacities during SARS-CoV-2 infection. Three additional patients who showed migratory pneumonia during SARS-CoV-2 infection had either X-linked agammaglobulinemia (XLA) [ 14 ], which is a condition characterized by an inability to produce B-cells, or were undergoing treatment with tirabrutinib [ 21 ], a Bruton’s tyrosine kinase (BTK) inhibitor that inhibits pathways associated with B-cell proliferation and development. In fact, BTK is known to be defective in XLA [ 33 ], and one study revealed that the pooled antibody responses after COVID-19 vaccination were the lowest (15% and 23%, respectively) for patients who had used anti-CD20 therapy within one year prior to COVID-19 diagnosis and a BTK inhibitor [ 34 ].…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation